Juridical Analysis Related To Confidentiality Of Notary Liability - D Djunaedi Djunaedi (Jurnal Daulat Hukum, 2021)
Notary protection related to confidentiality, especially in the law enforcement process, has not been able to materialize effectively. This is because there is no real protection system for notaries who reveal the confidentiality of their rights in the law enforcement process. This writing uses an empirical juridical method. As for the results of existing research, it can be found that the fact that the limitations of a notary in maintaining the confidentiality of a notary's duties based on the Notary's Position Law are that notaries must keep secrets related to their position. The notary is obliged to keep the contents of the act secret, even the notary is obliged to keep all information from the preparation of the deed to the completion of the drawing up of a deed and if he is made a witness in a case, can exercise his right to resign as a witness. However, it often happens that in a law enforcement process, a notary who is asked to assist in proof by disclosing the confidentiality of a deed that he has made can be sued and threatened by legal sanctions both in civil terms, namely acts against the law or for criminal reasons. Therefore, it is necessary to do more real legal protection for notaries who disclose the confidentiality of the deeds they have made for the sake of law enforcement.